Preparation method of Bi2WO6 / Bi4Ti3O12 for synergistically promoting photocatalytic degradation of organic dye methylene blue

The preparation of Bi2WO6/Bi4Ti3O12 composite material by hydrothermal method solves the problems of rapid recombination of photogenerated electrons and holes and low light utilization efficiency in photocatalysts, and achieves efficient degradation of methylene blue, which has environmental and economic advantages.

CN120838402APending Publication Date: 2025-10-28NINGXIA UNIVERSITY
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510981584.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-07-16
Publication Date
2025-10-28

AI Technical Summary

Technical Problem

Existing photocatalysts exhibit excessively rapid recombination of photogenerated electron-hole pairs during the degradation of methylene blue, resulting in low light utilization efficiency and consequently, low degradation efficiency. Traditional methods also suffer from high processing costs or the introduction of secondary pollution.

Method used

Bi2WO6 nanospheres were loaded onto irregular Bi4Ti3O12 nanosheets using a hydrothermal method to form a Bi2WO6/Bi4Ti3O12 composite material. The nanostructure was used to increase the specific surface area and improve the photocatalytic activity.

Benefits of technology

It achieved 99.9% degradation of 10 mg/L methylene blue solution within 180 minutes, demonstrating highly efficient and environmentally friendly catalytic performance. Furthermore, the material is simple to prepare, has good stability, and can be reused multiple times.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120838402A_ABST
    Figure CN120838402A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method of Bi2WO6 / Bi4Ti3O12 for synergistically promoting photocatalytic degradation of an organic dye methylene blue, irregular Bi4Ti3O12 nanosheets are loaded on Bi2WO6 nanospheres by using a hydrothermal method, the Bi2WO6 nanospheres are used for degrading methylene blue, nanocrystallized Bi2WO6 and Bi4Ti3O12 of a nanosheet structure have larger specific surface areas, more surface active sites are exposed, and the photocatalytic degradation of the organic dye methylene blue is promoted. The adsorption and catalytic degradation of methylene blue molecules are facilitated. The preparation process is simple, the degradation effect is excellent, and 99.9% of 10 mg L <-1 > methylene blue solution is finally degraded within 180 min through optimization of the initial concentration and pH.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to Bi2WO6 / Bi4Ti3O 12 In the field of preparation, this invention particularly relates to a Bi2WO6 / Bi4Ti3O4 composite material that synergistically promotes the photocatalytic degradation of the organic dye methylene blue. 12 Preparation method. Background Art

[0002] In recent years, environmental problems such as air and water pollution have become a global crisis affecting economic development and human health, prompting continuous basic and applied research in the field of environmental remediation. Visible light-driven photocatalysts have attracted widespread attention due to their superior performance in addressing environmental pollution. As a green and environmentally friendly pollution control method, photocatalysis technology, particularly semiconductor-based photocatalysis, has been extensively studied to address the energy crisis and alleviate environmental pollution, including solar-driven water splitting, pollutant degradation, nitrogen fixation, and the conversion of CO2 into valuable chemical fuels.

[0003] Among numerous photocatalytic materials, bismuth (Bi)-based photocatalysts have attracted considerable attention due to their excellent photocatalytic performance, environmental friendliness, and broad application prospects. In particular, Bi-based photocatalysts not only effectively degrade organic pollutants but also exhibit strong corrosion resistance and low toxicity, demonstrating significant application potential in pollutant treatment and environmental remediation. Especially in water pollution control, bismuth-based photocatalysts can degrade various persistent organic pollutants in water, including organic dyes and pharmaceutical compounds, thus showing great development potential.

[0004] Methylene blue (MB), chemically known as 3,7-bis(dimethylamino)phenothiazine-5-onium chloride, is an important phenothiazine salt compound. Since its first synthesis by the German chemist Heinrich Caro in 1876, it has demonstrated unique value in numerous fields. In the textile dyeing industry, methylene blue, with its beautiful blue color and good colorfastness, is widely used in the dyeing processes of silk, wool, cotton fabrics, paper, and leather, imparting to fabrics a lasting and vibrant color.

[0005] However, the widespread use of methylene blue has also brought a series of pollution problems. In industrial production processes, especially in the textile printing and dyeing industry, large amounts of wastewater containing methylene blue are discharged. This wastewater not only has a high color intensity, severely affecting the appearance of water bodies, but also, due to the relatively stable chemical structure of methylene blue, it is difficult to degrade naturally, causing it to persist in the environment. Over time, methylene blue-containing wastewater will cause serious pollution to the soil, water bodies, and other ecological environments, disrupting the ecological balance and affecting the survival and reproduction of aquatic organisms. For example, it may hinder sunlight from penetrating the water, affecting the photosynthesis of aquatic plants, and thus having a chain reaction on the entire aquatic ecosystem's food chain.

[0006] Current treatment methods for methylene blue have many shortcomings in addressing the pollution and hazards caused by its application. Traditional physical adsorption methods, such as activated carbon adsorption, can remove some methylene blue, but adsorbent regeneration is difficult and treatment costs are high. Chemical oxidation methods use strong oxidants to decompose methylene blue, but this may introduce new pollutants, and the reaction conditions are relatively harsh. Biological treatment methods are relatively environmentally friendly, but the adaptability and degradation efficiency of microorganisms to methylene blue need to be improved, and the treatment cycle is long.

[0007] To address the pollution problem caused by methylene blue, the development of more efficient, environmentally friendly, and economical treatment technologies is urgently needed. This will not only help reduce environmental pollution and safeguard ecological security and human health, but also promote the sustainable development of related industries. Therefore, exploring new methods and technologies for controlling methylene blue pollution has become a focus of attention for researchers and related enterprises, and has also provided ample space for the innovation and development of related patented technologies.

[0008] Photocatalysts currently face the following problems: (1) There is recombination between photogenerated electron-hole pairs. When recombination is too fast, the photogenerated electrons will not be able to complete the degradation; (2) The photocatalyst has low utilization efficiency of sunlight, which means that it can only absorb a portion of the energy, greatly reducing the degradation.

[0009] Compared with the literature (Ceramics International, 2025, 51, 11255-11266) on the degradation of methylene blue, the water-treated TiO2 / Bi2WO6 composite coating showed a degradation rate of only 75% for MB after 6 hours of visible light irradiation.

[0010] Bi₄Ti₃O₃ was synthesized via a hydrothermal method in the comparative literature (Journal of Alloys and Compounds, 2023, 955, 170168). 12 Nanosheets and flower-like MoS2 showed a removal efficiency of 91.1% in an initial MB solution of 10 mg / L within 270 minutes, but the degradation rate was less than 80% after 180 minutes. This invention, however, achieved a 99% removal efficiency in just 90 minutes at pH 9 and 11 through a simple hydrothermal reaction, transforming irregular Bi4Ti3O4 nanosheets and flower-like MoS2. 12 By loading Bi2WO6 nanospheres onto nanosheets, the materials used in the process are simple and pollution-free, and the prepared BWO / BTO photocatalyst has better catalytic activity and environmental friendliness.

[0011] Therefore, in view of the shortcomings of the existing technology, the present invention utilizes a hydrothermal method to process irregular Bi4Ti3O 12 Nanosheets loaded onto Bi2WO6 nanospheres for the degradation of methylene blue, nano-sized Bi2WO6 and nanosheet-structured Bi4Ti3O 12With a larger specific surface area and more exposed surface active sites, it is beneficial for the adsorption and catalytic degradation of methylene blue molecules. Summary of the Invention

[0012] In view of this, the present invention provides a Bi2WO6 / Bi4Ti3O4 compound that synergistically promotes the photocatalytic degradation of the organic dye methylene blue. 12 Preparation method.

[0013] To solve the above-mentioned technical problems, the present invention adopts the following technical solution:

[0014] A Bi2WO6 / Bi4Ti3O3 compound that synergistically promotes the photocatalytic degradation of the organic dye methylene blue 12 The preparation method includes the following steps:

[0015] Step 1: Bi4Ti3O 12 Preparation

[0016] Step 1.1: Dissolve Bi(NO3)3·5H2O in deionized water and label it as solution A;

[0017] Step 1.2: Add C to solution A 16 H 36 O4Ti, labeled as solution B;

[0018] Step 1.3: Add NaOH solution to solution B, followed by tert-butylamine and oleic acid;

[0019] Step 1.4: Carry out the hydrothermal reaction. After the reaction is complete, centrifuge and wash the precipitate. Place the washed precipitate in an oven to dry.

[0020] Step 2: Preparation of Bi2WO6

[0021] Step 2.1: Dissolve sodium tungstate and Bi(NO3)3·5H2O in deionized water and stir.

[0022] Step 2.2: Perform hydrothermal treatment on the solution, wash the product with deionized water and ethanol, and finally dry it;

[0023] Step 3: Bi2WO6 / Bi4Ti3O 12 Preparation

[0024] Step 3.1: Dissolve sodium tungstate and Bi(NO3)3·5H2O in deionized water, and simultaneously add Bi4Ti3O 12 Add the ingredients to the solution according to different molar ratios and stir.

[0025] Step 3.2: The solution was subjected to hydrothermal treatment, the product was washed with deionized water and ethanol, and finally dried in air to obtain Bi2WO6.

[0026] Preferably, in step 1.1, the amount of Bi(NO3)3·5H2O is 4 mmol, and the amount of deionized water added is 20 mL.

[0027] Preferably, in step 1.2, C 16 H 36 The amount of O4Ti was 3 mmol.

[0028] Preferably, in step 1.3, the molar concentration of the NaOH solution is 3 mol / L, and the amount added is 40 mL;

[0029] The amount of tert-butylamine was 12 mmol, and the amount of oleic acid was 6 mmol.

[0030] Preferably, in step 1.4, the hydrothermal reaction temperature is 180°C and the hydrothermal reaction time is 24 hours.

[0031] Preferably, in step 2.1, the amount of sodium tungstate is 1 mmol, the amount of Bi(NO3)3·5H2O is 2 mmol, the amount of deionized water added is 30 mL, and the stirring time is 30 min.

[0032] Preferably, in step 2.2, the hydrothermal treatment temperature is 120°C and the hydrothermal treatment time is 24 hours.

[0033] The product was washed three times with deionized water and ethanol, and dried at 60°C.

[0034] Preferably, in step 3.1, the amount of sodium tungstate is 1 mmol, the amount of Bi(NO3)3·5H2O is 2 mmol, the amount of deionized water added is 30 mL, and the stirring time is 30 min.

[0035] Preferably, in step 3.1, the different molar ratios are BWO / BTO = 0.5:1; 1.1; 2:1.

[0036] Preferably, in step 3.2, the hydrothermal treatment temperature is 120°C and the hydrothermal treatment time is 24 hours.

[0037] The product was washed three times with deionized water and ethanol and dried in air at 60°C.

[0038] The present invention achieves the following technical effects compared to the prior art:

[0039] (1) This invention utilizes a hydrothermal method to process irregular Bi4Ti3O 12Nanosheets loaded onto Bi2WO6 nanospheres for the degradation of methylene blue, nano-sized Bi2WO6 and nanosheet-structured Bi4Ti3O 12 With a larger specific surface area and more exposed surface active sites (such as hydroxyl groups), it is beneficial for the adsorption and catalytic degradation of methylene blue molecules;

[0040] (2) The preparation process of this invention is simple and the degradation effect is excellent. After optimization of the initial concentration and pH, 10 mg L of the solution was finally degraded within 180 min. -1 The methylene blue solution is 99.9%. Attached Figure Description

[0041] Figure 1 The X-ray diffraction (XRD) pattern of the composite sample of this invention;

[0042] Figure 2 (ac) is the SEM image of BWO, BTO and BWO / BTO of the present invention; (de) is the TEM image and HRTEM image of BWO / BTO of the present invention; (fj) is the EDS image of BWO / BTO of the present invention.

[0043] Figure 3 (a) is the 10mg L of the present invention. -1 (a) Degradation curve of methylene blue; (b) First-order kinetic curve of the present invention; (c) Distribution of kinetic constants of the present invention; (d) Experimental curve of cyclic degradation of methylene blue of the present invention;

[0044] Figure 4 (a) is a graph showing the degradation of methylene blue at different initial concentrations according to the present invention; (b) is a graph showing the first-order kinetics of the present invention; (c) is a graph showing the distribution of kinetic constants of the present invention.

[0045] Figure 5 (a) is a graph showing the decrease of MB in different solutions at different pH levels according to the present invention; (b) is a graph showing the first-order kinetics of the present invention; (c) is a graph showing the distribution of kinetic constants of the present invention. Detailed Implementation

[0046] The following will clearly and completely describe the technical solutions in the embodiments of the present invention in conjunction with the accompanying drawings. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative efforts are within the scope of protection of the present invention.

[0047] This invention discloses a Bi2WO6 / Bi4Ti3O4 compound that synergistically promotes the photocatalytic degradation of the organic dye methylene blue. 12 The preparation method includes the following steps:

[0048] Step 1: Bi4Ti3O 12 Preparation

[0049] Step 1.1: Dissolve 4 mmol of Bi(NO3)3·5H2O in 20 mL of deionized water, labeling this solution A; Step 1.2: Add C to solution A. 16 H 36 O4Ti (3 mmol) labeled solution B;

[0050] Step 1.3: Add 40 mL of 3 mol / L NaOH solution to solution B, followed by 12 mmol of tert-butylamine (TB) and 6 mmol of oleic acid (OA);

[0051] Step 1.4: Perform a hydrothermal reaction at 180℃ for 24 hours. After the reaction is complete, centrifuge and wash the precipitate, then place the washed precipitate in an oven to dry.

[0052] Step 2: Preparation of Bi2WO6

[0053] Step 2.1: Dissolve 1 mmol of sodium tungstate and 2 mmol of Bi(NO3)3·5H2O in 30 mL of deionized water and stir for 30 min;

[0054] Step 2.2: The solution was subjected to hydrothermal treatment by reacting at 120℃ for 24h. The product was washed three times with deionized water and ethanol, and finally dried at 60℃.

[0055] Step 3: Bi2WO6 / Bi4Ti3O 12 Preparation

[0056] Step 3.1: Dissolve 1 mmol of sodium tungstate and 2 mmol of Bi(NO3)3·5H2O in 30 mL of deionized water, and simultaneously add Bi4Ti3O 12 Add the ingredients to the solution according to different molar ratios and stir for 30 minutes;

[0057] Step 3.2: The solution was subjected to hydrothermal treatment at 120℃ for 24 hours. The product was washed three times with deionized water and ethanol, and finally dried in air at 60℃ to obtain Bi2WO6; the different molar ratios were BWO / BTO = 0.5:1; 1.1; 2:1.

[0058] Example 1: Structural and morphological characterization of BWO / BTO composite materials

[0059] First, the microcrystalline structure of the BWO / BTO composite material was analyzed by XRD.

[0060] like Figure 1 The figures shown are Bi2WO6 and Bi4Ti3O.12 The XRD patterns of composite materials with different composite ratios were also obtained. The diffraction peaks of the prepared Bi2WO6 at 2θ = 28.30°, 32.92°, 47.15°, 56.0°, 76.0°, and 78.2° correspond one-to-one with the crystal planes (113), (200), (202), (331), (333), and (064), respectively. There are not many impurity peaks, indicating that the Bi2WO6 monomer has been successfully prepared.

[0061] Bi4Ti3O synthesized by hydrothermal method 12 It matches well with the standard card PDF#35-0795 and contains no extraneous impurity peaks, indicating that Bi4Ti3O 12 Monomers have also been successfully prepared. Composite materials, in addition to Bi2WO6 and Bi4Ti3O, include... 12 Besides the diffraction peaks, there were no obvious impurity peaks, proving that different proportions of Bi2WO6 / Bi4Ti3O 12 The composite material was successfully prepared.

[0062] The morphology of monomers and composite materials was observed using scanning electron microscopy (SEM) and transmission electron microscopy (TEM).

[0063] like Figure 2 As shown in (ac), Bi2WO6 is composed of nanospheres assembled from nanosheets, with a size of approximately 2 μm. Bi4Ti3O 12 The composite BWO / BTO exhibits irregular nanosheets, with the irregular BTO nanosheets loaded on BWO nanospheres.

[0064] like Figure 2 As shown in (d), the composite is an irregular nanosheet BTO loaded on BWO nanospheres;

[0065] like Figure 2 As shown in (e), the lattice spacing of BWO was measured to be 0.27 nm, and the lattice spacing of MoS2 was measured to be 0.29 nm. This indicates that the composite was successfully prepared.

[0066] Energy dispersive spectroscopy (EDS) such as Figure 2 As shown in (fj), the composite material BWO / BTO contains Bi, O, Ti and W elements, and BTO is loaded on the surface of BWO sheets, further confirming the successful synthesis of BWO / BTO.

[0067] Example 2: Performance test of photocatalytic degradation of dye MB

[0068] Measure 100 mL of a 10 mg / L MB solution into a beaker. Add 30 mg of photocatalyst to the MB solution and stir the mixture thoroughly for 60 min under light-protected conditions to reach desorption-adsorption equilibrium. Irradiate the mixture containing the photocatalyst using a 300 W xenon lamp to simulate sunlight for a total of 3 h. Take 3 mL samples every 30 min and place them in a test tube. After catalysis, centrifuge the collected samples and collect the supernatant. Measure the absorbance of the supernatant at 664 nm using a UV spectrophotometer. Calculate the dye degradation rate (D) based on the absorbance.

[0069] D = (C0 - C) t ) / C0×100%

[0070] In the formula: D is the degradation efficiency, C0 is the absorbance of the initial dye concentration, and C t This represents the absorbance during the degradation process.

[0071] The cyclic experiment involves centrifuging the solution after the experiment, collecting the precipitate, drying it, and then repeating the experimental procedure.

[0072] like Figure 3 As shown in (a), different catalysts Bi2WO6 and Bi4Ti3O are used. 12 The photocatalytic degradation effects of 0.5 BWO / BTO, BWO / BTO, and 2 BWO / BTO on MB were investigated. The results showed that all photocatalysts had some effect on MB degradation, with BWO / BTO showing the best effect, achieving a degradation rate of 85% within 3 hours.

[0073] Experimental results show that Bi2WO6 can effectively improve the performance of Bi4Ti3O 12 The photocatalytic degradation function of photocatalysts. The photocatalytic degradation of MB follows a pseudo-first-order reaction kinetic equation (-ln(Ct / Co=kt), and the reaction rate constant k follows a pseudo-first-order reaction as follows: Figure 3 As shown in c.

[0074] After linear fitting of the curves, the k-values ​​for each sample were calculated to obtain the values ​​for Bi2WO6 and Bi4Ti3O. 12 The reaction rate constants for 0.5 BWO / BTO, 0.5 BWO / BTO, and 2 BWO / BTO are 0.00346 min. -1 0.00277min -1 0.00277min -1 0.00909min -1 0.00732min -1 .

[0075] Depend on Figure 3As shown in (b) and (c), the BWO / BTO value is the highest, which further illustrates the relationship between Bi2WO6 and Bi4Ti3O. 12 It has a synergistic effect and can improve its photocatalytic performance.

[0076] To determine the stability of BWO / BTO, five replicate experiments were conducted. The remaining sample after each catalytic experiment was collected by centrifugation and used in the next catalytic experiment. Figure 3 As shown in (d), the degradation efficiency of BWO / BTO on MB did not decrease significantly in 5 cycles, indicating that BWO / BTO has good stability and can be recycled and reused multiple times.

[0077] The concentration of dye has a significant impact on the performance of photocatalytic degradation of dye.

[0078] like Figure 4 As shown in (a), the degradation performance of MB decreases continuously with increasing MB concentration, from 85% to 5.35%, so the optimal concentration is 10 mg / L. Too much or too little MB will lead to a decrease in photocatalytic efficiency.

[0079] Its degradation curve can be obtained by linear fitting as follows: Figure 4 As shown in (bc), it is still clear that a concentration of 10 mg / L is the most appropriate concentration.

[0080] pH is one of the factors affecting catalytic performance. Because dyes are classified as acidic or basic based on pH, the hydrogen and hydroxide ions dispersed in the solution can react with electrons or holes on the catalyst surface, thus affecting catalytic performance.

[0081] To investigate the degradation effect of BWO / BTO at different pH values, five pH values ​​(3, 5, 7, 9, 11) were set up, and the degradation rate was investigated with pH value using 30 mg / L MB solution.

[0082] Depend on Figure 5 (a) It can be seen that MB is an alkaline organic dye, which is more easily degraded in alkaline media with a degradation rate of 99.9%. Conversely, the degradation rate is greatly reduced in acidic media. This is because the catalyst surface is positively charged in acidic media (pH<7) and negatively charged in alkaline media (pH>7). When pH<7, the catalyst and MB solution will repel each other, reducing the degradation performance. When pH>7, the catalyst is negatively charged and thus adsorbs pollutants, greatly improving the degradation performance.

[0083] Depend on Figure 5 (bc) The first-order kinetic fitting curve and K value also intuitively reflect the changing law of pH value on degradation rate.

[0084] The above description is merely a preferred embodiment of the present invention and does not constitute any limitation on the technical scope of the present invention. Therefore, any minor modifications, equivalent changes, and alterations made to the above embodiments based on the technical essence of the present invention shall still fall within the scope of the technical solution of the present invention.

Claims

1. A Bi2WO6 / Bi4Ti3O3 compound that synergistically promotes the photocatalytic degradation of the organic dye methylene blue. 12 Preparation method, characterized in that, Includes the following steps: Step 1: Bi4Ti3O 12 Preparation Step 1.1: Dissolve Bi(NO3)3·5H2O in deionized water and label it as solution A; Step 1.2: Add C to solution A 16 H 36 O4Ti, labeled as solution B; Step 1.3: Add NaOH solution to solution B, followed by tert-butylamine and oleic acid; Step 1.4: Carry out the hydrothermal reaction. After the reaction is complete, centrifuge and wash the precipitate. Place the washed precipitate in an oven to dry. Step 2: Preparation of Bi2WO6 Step 2.1: Dissolve sodium tungstate and Bi(NO3)3·5H2O in deionized water and stir. Step 2.2: Perform hydrothermal treatment on the solution, wash the product with deionized water and ethanol, and finally dry it; Step 3: Bi2WO6 / Bi4Ti3O 12 Preparation Step 3.1: Dissolve sodium tungstate and Bi(NO3)3·5H2O in deionized water, and simultaneously add Bi4Ti3O 12 Add the ingredients to the solution according to different molar ratios and stir. Step 3.2: The solution was subjected to hydrothermal treatment, the product was washed with deionized water and ethanol, and finally dried in air to obtain Bi2WO6.

2. The Bi2WO6 / Bi4Ti3O3 synergistically promotes the photocatalytic degradation of the organic dye methylene blue according to claim 1. 12 Preparation method, characterized in that, In step 1.1, the amount of Bi(NO3)3·5H2O is 4 mmol, and the amount of deionized water added is 20 mL.

3. The Bi2WO6 / Bi4Ti3O3 synergistically promotes the photocatalytic degradation of the organic dye methylene blue according to claim 1. 12 Preparation method, characterized in that, In step 1.2, C 16 H 36 The amount of O4Ti was 3 mmol.

4. The Bi2WO6 / Bi4Ti3O3 synergistically promotes the photocatalytic degradation of the organic dye methylene blue according to claim 1. 12 Preparation method, characterized in that, In step 1.3, the molar concentration of the NaOH solution is 3 mol / L, and the amount added is 40 mL; The amount of tert-butylamine was 12 mmol, and the amount of oleic acid was 6 mmol.

5. The Bi2WO6 / Bi4Ti3O3 synergistically promotes the photocatalytic degradation of the organic dye methylene blue according to claim 1. 12 Preparation method, characterized in that, In step 1.4, the hydrothermal reaction temperature is 180℃ and the hydrothermal reaction time is 24h.

6. The Bi2WO6 / Bi4Ti3O3 synergistically promotes the photocatalytic degradation of the organic dye methylene blue according to claim 1. 12 Preparation method, characterized in that, In step 2.1, the amount of sodium tungstate is 1 mmol, the amount of Bi(NO3)3·5H2O is 2 mmol, the amount of deionized water added is 30 mL, and the stirring time is 30 min.

7. The Bi2WO6 / Bi4Ti3O3 synergistically promotes the photocatalytic degradation of the organic dye methylene blue according to claim 1. 12 Preparation method, characterized in that, In step 2.2, the hydrothermal treatment temperature is 120℃ and the hydrothermal treatment time is 24h. The product was washed three times with deionized water and ethanol, and dried at 60°C.

8. The Bi2WO6 / Bi4Ti3O3 synergistically promotes the photocatalytic degradation of the organic dye methylene blue according to claim 1. 12 Preparation method, characterized in that, In step 3.1, the amount of sodium tungstate is 1 mmol, the amount of Bi(NO3)3·5H2O is 2 mmol, the amount of deionized water added is 30 mL, and the stirring time is 30 min.

9. The Bi2WO6 / Bi4Ti3O3 synergistically promotes the photocatalytic degradation of the organic dye methylene blue according to claim 1. 12 Preparation method, characterized in that, In step 3.1, the different molar ratios are BWO / BTO = 0.5:1; 1.1; 2:

1.

10. The Bi2WO6 / Bi4Ti3O3 compound according to claim 1 that synergistically promotes the photocatalytic degradation of the organic dye methylene blue. 12 Preparation method, characterized in that, In step 3.2, the hydrothermal treatment temperature is 120℃ and the hydrothermal treatment time is 24h. The product was washed three times with deionized water and ethanol and dried in air at 60°C.